Neurocognitive aspects of body size estimation - A study of contemporary dancers - André Bizerra; Eliane Florencio Gama
Abstract Dancers use multiple forms of body language when performing their functions in the contemporary dance scene. Some neurocognitive aspects are involved in dance, and we highlight the aspect of body image, in particular, the dimensional aspect of the body perception. The aim of this study is to analyze the perceptual aspect of body image (body size estimation) and its possible association with the motor aspect (dynamic balance) involved in the practice of dance, comparing contemporary dancers with physically active and inactive individuals. The sample consisted of 48 subjects divided into four groups: 1) Professional Group (PG); 2) Dance Student Group (SG); 3) Physically Active Group (AG); and 4) Physically Inactive Group (IG).Two tests were used: the Image Marking Procedure (body size estimation) and the Star Excursion Balance Test (dynamic balance). Was observed that dancing and exercising contribute to a proper body size estimation, but cannot be considered the only determining factor. Although dancers have higher ability in the motor test (dynamic balance), no direct relation to the perception of body size was observed, leading us to conclude it is a skill task/dependent acquired by repeating and training. In this study, we found a statistical significant association between educational level and body size estimation. The study opens new horizons in relation to the understanding of factors involved in the construction of the body size estimation.